PELATIHAN DESAIN KEMASAN SEBAGAI UPAYA PENINGKATAN HASIL PENJUALAN PRODUK DI KOPERASI PRODUSEN BIREUEN RAYA SEJAHTERA JEUNIEB KABUPATEN BIREUEN - Zulfikar (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2023)
This community service activity is entitled "Packaging Design Training as an Effort to Increase Product Sales Results at the Jeunieb Bireuen Raya Sejahtera Producer Cooperative, Bireuen Regency". The aim of this training activity is to provide knowledge and train participants how to design packaging using the Canva application for the products being sold to make it more attractive and creative. This training activity was carried out in September 2023 for 2 days with 15 MSME participants and members of the Bireuen Raya Sejahtera Jeunieb Producer Cooperative. Meanwhile, the benefits that participants get from training activities are increased knowledge, insight and skills of participants on how to design attractive and creative packaging through the Canva application. The result of this service activity is that participants are very enthusiastic about taking part in the training and are starting to be able to design packaging that is unique and appropriate to the products they sell.